Sistem Basis Data Manajemen Akademik dengan Platform Web pada Sekolah Menengah Atas Muhammadiyah 4 Bandung - Ayu Hidayah Aslamia; Herru Darmadi (Engineering, MAthematics and Computer Science (EMACS) Journal, 2020)
The purpose of this research is to design a database system that is implemented in a web-based academic management that can be used to support the information system and academic management at Muhammadiyah 4 High School Bandung. The proposed Method in system design includes 2 parts, such as system analysis and product design. Analytical methods include literature studies, interviews, and questionnaire. Meanwhile, the database design method used are three stages database design according to Connoly and Begg. The results achieved are web based academic and database management system at Muhammadiyah High School 4 Bandung. The conclusion obtained from this research is the system is able to provide information needs, faster, accurate, prevent duplication problem of data , to support decision making, to improve effective communication between the user, and to get the information easier.